EFFECT OF TROUT FISH LIVER EXTRACT ON GROWTH AND DEVELOPMENT OF RABBIT (E Conference Zone, 2022)
In this article, studies were conducted to study the effect of trout liver extract on the growth and development of rabbits and the results obtained are described.